A Long-Term Follow-up of Retinal Vasculitis – Do They Develop Systemic Disease?. (16th November 2020) - Kawali, Ankush; Bavaharan, Bharathi; Sanjay, Srinivasan; Mohan, Ashwin; Mahendradas, Padmamalini; Shetty, Bhujang
ABSTRACT: Purpose : To study systemic association and relapses in a long-term follow-up of primary retinal vasculitis (PRV) and possible tubercular vasculitis (PTV) cases. Method : Retrospective, descriptive chart review of patients diagnosed as PRV and PTV with ≥1-year follow-up. Clinical presentation, systemic association, morphology of vasculitis, relapses, and treatment were noted. Results : 123 eyes of 76 patients were studied. Occlusive (n = 97), exudative (n = 16), combined (n = 10) and focal (n = 7) vasculitis were seen. Vitreous hemorrhage at presentation was noted in 27% eyes (n = 33). Four patients (3.25%) developed systemic disease during follow-up (2 psoriasis, 1 Systemic Lupus Erythematosus, 1 ulcerative colitis). Mean number of cases with relapses were 45 (59.21%). Number of cases with relapses in PRV and PTV were 20 (66.66%) and 16 (66.66%), respectively. ( p = 1) Conclusion : Systemic disease attributed to vasculitis can rarely develop during follow up of PRV and PTV patients. Relapses remain almost same in PTV and PRV.